Optimization of cardamom fruit ethanol extract gel with combination of HPMC and Sodium Alginate as the gelling agent using Simplex Lattice Design - Wati Eliana Putri; Metha Anung Anindhita (Jurnal Ilmiah Farmasi, 2022)
AbstractBackground: Cardamom has been studied and proven to be effective as an antibacterial. Gel preparations are preferred because they have advantages such as being easy to apply, providing a cooling effect, and being able to deliver drugs well.Objective: The purpose of this study was to make a gel formulation of ethanolic cardamom fruit extract by optimizing the combination of the gelling agent of HPMC and sodium alginate using the simplex lattice design (SLD).Methods: Cardamom fruit extract was obtained by extracting cardamom fruit simplicia using 70% ethanol. The formulation of the gel preparation from cardamom fruit extract was optimized using the SLD method on Design Expert. There were 5 gel formulas made and evaluated including organoleptic, pH, viscosity, spreadability, and adhesion. The independent variables in SLD were the amount of HMC and sodium alginate, while the responses included viscosity, spreadability, and adhesion. Optimal formula selection is done by using a numerical approach.Results: FI (HPMC 3.75% and sodium alginate 2.75%) and FII (HPMC 3.50% and sodium alginate 3.00%) met the test criteria for all the tests performed. The optimal formula suggested by SLD is a combination of 3.53% HPMC and 2.98% sodium alginate with a desirability value of 1.00. The predicted value for each response was the viscosity of 214.83 dPa.s, dispersion of 5.38 cm, and adhesion of 50.08 seconds. The optimal formula showed a dispersion value of 5.37cm. The results of the t-test indicated that the dispersion value of the observed results is not significantly different from the prediction software.Conclusion: Based on this research, it can be concluded that the use of a combination of HPMC and sodium alginate as a gelling agent can be optimized by using a simplex lattice design to obtain the optimum formula for cardamom fruit extract gel.Keywords: gel, hpmc, sodium alginate, SLD, kapulaga IntisariLatar Belakang: Kapulaga telah diteliti dan terbukti dapat dimanfaatkan sebagai antibakteri. Sediaan gel disukai karena memiliki keunggulan antara lain mudah merata bila dioleskan, memberikan efek dingin serta dapat menghantarkan obat dengan baik.Tujuan: Penelitian ini bertujuan untuk membuat formulasi sediaan gel ekstrak buah kapulaga dengan mengoptimasi penggunaan kombinasi gelling agent HPMC dan natrium alginat menggunakan metode Simplex Lattice Design (SLD). Metode: Ekstrak buah kapulaga diperoleh dengan mengekstraksi simplisia buah kapulaga menggunakan etanol 70%. Formulasi sediaan gel dari ekstrak buah kapulaga dioptimasi menggunakan metode SLD pada Design Expert. Terdapat 5 formula gel yang dibuat dan dievaluasi meliputi organoleptis, pH, viskositas, daya sebar, dan daya lekat. Variabel bebas pada SLD adalah jumlah HMC dan natrium alginat, sedangkan responnya meliputi viskositas, daya sebar, dan daya lekat. Pemilihan formula optimum dilakukan menggunakan pendekatan numerical.  Hasil: FI (HPMC 3,75% dan natrium alginat 2,75%) dan FII (HPMC 3,50% dan natrium alginat 3,00%) memenuhi kriteria uji semua pengujian yang dilakukan. Formula optimal yang disarankan SLD adalah kombinasi HPMC 3,53% dan natrium alginat 2,98% memiliki desirability 1,00 dengan prediksi viskositas bernilai 214,83 dPa.s, daya sebar bernilai 5,38 cm, dan daya lekat 50,08 detik. Pengujian terhadap formula optimal hasil optimasi SLD menunjukkan nilai daya sebar 5,37cm sesuai dengan nilai respon pada SLD. Hasil uji-t menunjukkan nilai daya sebar hasil observasi tidak berbeda signifikan dibandingkan dengan prediksi software.Kesimpulan: Berdasarkan penelitian ini dapat disimpulkan bahwa penggunaan variasi HPMC dan natrium alginat sebagai gelling agent dalam formula gel ekstrak buah kapulaga dapat dioptimasi menggunakan simplex lattice design.Kata kunci : gel, hpmc, natrium alginat, SLD, kapulaga